Future hype : the myths of technology change - Seidensticker, Robert B., 1957- (Berrett-Koehler Publishers ; Publishers Group West [distributor], 2006)
The general public has come to accept that technology is the greatest new growth frontier with an infinite amount of potential. Conventional thinking states that never before has such a golden era existed in which technology thrived and blossomed so fully. This work deals with this kind of hype.